Teacher Spiritual Competence in Shaping the Personality of Madrasah Tsanawiyah Students - Ahmad Fuad Bahalwan; Ali Ahmad Yenuri (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
The teacher is not the one who just teaches in front of the class without any competency. However, a teacher must have certain competencies so that they can carry out their duties properly. The teacher is an unsung hero who sacrifices his mind and energy to educate a student to be better physically and spiritually. So spiritual competence is the ability of a teacher to maintain the spirit that teaching is worship with the aim of only hoping for the pleasure of Allah alone. The formulation of the problems in this study are: (1) How is the process of forming students' personalities through the spiritual competence of class IX teachers at MTs SA Al-Hidayah Konang Bangkalan. (2) What are the supporting and inhibiting factors in the formation of the personality of class IX students at MTs SA Al-Hidayah Konang Bangkalan. This research method uses a descriptive qualitative approach, data analysis uses data reduction, data presentation and conclusion, so that the data is descriptive in nature, while the data collection technique uses observation, interviews, and documentation, and for data validity using triangulation with sources, technique and time. The results of the study show that shaping a child's personality does not occur spontaneously or directly, requires a process and also includes several elements of the spiritual competence of a good teacher, and is wise in carrying out tasks, manifested by teacher behavior that is in accordance with religious norms, not easily angry- angry at students who make mistakes, but will give advice and direction. The supporting and inhibiting factors are as follows: (a) Supporting factors: (1) Family environment, (2) Community or social environment. (b) Inhibiting factors: (1) Limited supervision by the school. (2) Weak student awareness.